Technical Wording in Advertising: Implications for Market Segmentation - Anderson, Rolph E. and Jolson, Marvin A. (Journal of Marketing, 1980)
It may be ill-advised for advertisers to avoid technical language in print media messages directed to household consumers. Results of an experiment reported here suggest that technical wording levels in ads combine with the audience's educational levels and product experience to generate a series of product perceptions, advertising evaluations, and purchase considerations.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS8xMjUwMDM1